TIPS TO STAY FOCUSED WHILE READING - PhD, Docent Adash Eshankulovna Rustamova; Abdullayeva Iroda Sabirovna (Scholar Express Journals, 2023)
In this article there are some top tips of concentration of students while reading. Hope you can read this article and learn and follow these strategies
Keywords: practice meditation; take notes; highlights; pomodora method